(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Damage to buildings and other structures may occur when dynamic loads, caused by earthquake vibrations, drive the ground and everything related to it to shake in a complicated way. Civil engineers are always thinking of new methods to deal with this inevitable problem. Humans put stress on a variety of buildings, including floors, footbridges, stadiums, and more. Modern material and manufacturing technology, together with human desire for aesthetics, have made it possible to build long span structures like bridges, stadiums, floors, etc. that are sleek, lightweight, and slim. To dampen a structure’s dynamic reaction, engineers use devices called (TMDs), which consist of a mass and a spring, are tuned mass dampers. When it comes to managing the structural reactions to wind and harmonic excitations, Tuned Mass Damper (TMD) is the way to go. Specifically, the shear beam and 1D lumped-mass beams are the models under consideration. The main purpose of this piece is to demonstrate how methods that use records of ambient vibration may enhance and supplement seismic risk assessments of preexisting structures. To compare the structure’s reaction with and without TMD, or tuned mass damper, is mounted on the building’s exterior. Using a model calculated from outside vibrations and recorded within the structure, we were able to effectively compare the building’s motion to a fake ground motion. It was also determined the inter-storey drift and the stiffness of each floor.